On the Capital Structure of Foreign Subsidiaries: Evidence from a Panel Data Quantile Regression Model - Raffaele Miniaci; Paolo Panteghini (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper studies how variations in tax rates and profitability affect the (unconditional) quantiles of the distribution of the leverage of European foreign owned subsidiaries in the presence of unobserved company characteristics, possibly correlated with their observable dimensions. To achieve our goal, we suggest how to apply Firpo et al. (2009) approach to the estimation of unconditional quantile partial effects in a model with correlated random effects. The results show that the impact of taxes and profitability on subsidiaries' financial choices varies across different quantiles of the (skewed) distribution of leverage. In particular, when the leverage ratio is low enough, an increase in a subsidiary's tax rate stimulates its borrowing. When however, the leverage ratio is high enough, taxes do not matter. We also find that the parent company's tax rate has a positive impact on a subsidiary's leverage ratio only if its starting leverage ratio is low enough. Finally, profitability (proxied by ROA) has either a negative or null impact, depending on the leverage ratio and the tax rate used (namely, statutory or effective marginal tax rates).
Keywords: C23; C21; G32; H25; 330; panel data; quantile regression; corporate finance